The relationship between principal leadership and teacher practice: Exploring the mediating effect of teachers' beliefs and professional learning - Er, Emre (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2024)
The study intended to explore whether and to what extent principal learning-centred leadership influences teacher practices, with the mediating role of teacher beliefs and teacher professional learning. The study gathered data from 426 teachers working in kindergarten, primary, secondary, and high schools. A cross-sectional survey design was employed and performed confirmatory factor analysis, structural equation modelling, and bootstrapping to analyse the data. The results confirmed positive and significant relationships among study variables. Learning-centred leadership has positive and moderate indirect effects on teacher changed through teacher beliefs and teacher professional learning. The research contributes to a growing body of research that confirms a positive link between principal leadership and teacher practice and highlights the salience of teacher beliefs and teacher professional learning in promoting teacher change in instructional practices to better meet the heightened expectations for student achievement.
Keywords: Principal learning-centred leadership; teacher leadership; teacher agency; teacher changed practice; turkey; CENTERED LEADERSHIP; TRANSFORMATIONAL LEADERSHIP; ACADEMIC OPTIMISM; SCHOOL LEADERSHIP; ACHIEVEMENT; CHINA; COMMUNITIES; INSTRUCTION; COMMITMENT; PATHWAYS; Education & Educational Research